2021
DOI: 10.3390/cancers14010137
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Stromal Cells Promote the Contribution of MMP2-Positive Bone Marrow-Derived Cells to Oral Squamous Cell Carcinoma Invasion

Abstract: Tumor stromal components contribute to tumor development and invasion. However, the role of stromal cells in the contribution of bone marrow-derived cells (BMDCs) in oral squamous cell carcinoma (OSCC) invasion is unclear. In the present study, we created two different invasive OSCC patient-derived stroma xenografts (PDSXs) and analyzed and compared the effects of stromal cells on the relation of BMDCs and tumor invasion. We isolated stromal cells from two OSCC patients: less invasive verrucous OSCC (VSCC) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Specifically, in parallel with the increase in the number of infiltrating leukocytes, the levels of the abovementioned cytokines progressively augment as the oral mucosa becomes the site of a chronic inflammation, an OPMD, and, finally, an invasive OSCC [79,108,109]. This phenomenon has been confirmed in animal models of oral carcinogenesis [110,111]. On their part, OSCC cells constitutively express IL-1, IL-6, IL-8, and TNF-α, thereby contributing to increasing the concentration of these inflammatory mediators in the tumor tissue [112][113][114][115].…”
Section: Reciprocal Interaction Between Cd147 and Opmd/oscc-associate...mentioning
confidence: 93%
“…Specifically, in parallel with the increase in the number of infiltrating leukocytes, the levels of the abovementioned cytokines progressively augment as the oral mucosa becomes the site of a chronic inflammation, an OPMD, and, finally, an invasive OSCC [79,108,109]. This phenomenon has been confirmed in animal models of oral carcinogenesis [110,111]. On their part, OSCC cells constitutively express IL-1, IL-6, IL-8, and TNF-α, thereby contributing to increasing the concentration of these inflammatory mediators in the tumor tissue [112][113][114][115].…”
Section: Reciprocal Interaction Between Cd147 and Opmd/oscc-associate...mentioning
confidence: 93%
“…In mice, bone marrow transplantation (BMT) via the tail vein is favorably applicable to trace the plasticity of bone marrow-derived cells in diseases including bone healing and cancers. (11)(12)(13)(14)(15) The studies on BMT models have shown that bone marrow-derived cells are distributed to myofibroblasts and fibroblasts in multiple organs, chondrocytes, and osteoblasts in bone, and tumor endothelium and cancerassociated stromal cells in the tumor microenvironment. (16) However, some studies on BMT models revealed that bone marrow cells did not differentiate into osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a higher proportion of stroma in OSCC relates to poor prognosis [ 4 , 5 ]. We also observed that incorporating different stromal cells into oral cancer xenograft models showed different effects on tumor progression, bone invasion, and bone marrow cell recruitment [ 6 , 7 ]. On the other hand, tumor angiogenesis supports tumor development, dissemination, and metastasis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%